Alcohol Fixation of Induced Sputum Samples for Applications in Rural Communities - Sandra C Dorman; Melanie A Bussoli; Stacey A Ritz (Canadian Respiratory Journal)
BACKGROUND: Sputum induction is a tool recommended for the assessment of airway inflammation and disease management. Currently, its use is limited because samples need to be processed within 3 h of induction (ie, while cells are viable); therefore, this procedure is unavailable to most clinicians.